24-Epibrassinolide alleviates organic pollutants-retarded root elongation by promoting redox homeostasis and secondary metabolism in Cucumis sativus L. (October 2017) - Ahammed, Golam Jalal; He, Bei-Bei; Qian, Xiang-Jie; Zhou, Yan-Hong; Shi, Kai; Zhou, Jie; Yu, Jing-Quan; Xia, Xiao-Jian
Abstract: Environmental pollution by organic pollutants (OPs) has become a global concern due to its detrimental effects on the environment and human health. As plants are used to remediate contaminated sites, understanding the responses of plants to various OPs and fortification of plant tolerance are of great significance. In this work, we studied the biochemical and molecular responses of cucumber plants to three well-known OPs, 2, 4, 6-trichlorophenol, chlorpyrifos and oxytetracycline in the absence or presence of 24-epibrassinolide (EBR), a potent regulator of plant growth and stress tolerance. The results showed that the selected three OPs retarded root elongation; however, the phytotoxic effects of OPs were attenuated by exogenous EBR. OPs induced accumulations of both hydrogen peroxide (H2 O2 ) and nitric oxide (NO) in root tips and resulted in an increased malondialdehyde (MDA) content, an indicator of membrane lipid peroxidation. Exogenous EBR reduced accumulations of H2 O2, NO and MDA in the roots by increasing the expression of antioxidant and detoxification genes and the activities of the corresponding enzymes. Intriguingly, EBR not only promoted the activities of glutathione S -transferase and glutathione reductase, but also increased the content of reduced glutathione without altering the content of oxidized glutathione, which resulted in a reduced redox state under OPs stress. Furthermore, EBR increased the free radical scavenging capacity, flavonoid content and the activity and transcription of secondary metabolism related enzymes. Our results suggest that EBR treatment may fortify secondary metabolism to enhance antioxidant capacity in response to OPs treatment, which might have potential implication in phytoremediation of OPs. Graphical abstract: Highlights: Organic pollutants (OP) inhibited cucumber root elongation in a dose-dependent manner. 24-epibrassinolide (EBR) reduced OP-induced accumulation of MDA, H2 O2 and NO in roots. EBR increased glutathione content, leading to a more reduced cellular redox status. EBR increased the free radical scavenging capacity and flavonoid content. Abstract : 24-epibrassinolide-promoted tolerance to organic pollutants is associated with improved antioxidant potential, redox homeostasis and secondary metabolism in cucumber.